EDUCATION VIDEO “GEMITA” (GEMAR MENCUCI TANGAN) AS AN OPTIMIZATION STEP FOR 6 STEPS HAND WASHING BEHAVIOR IN KINDERGARTEN CHILDREN - Fatmawati, Lilis; Qomariya Eka Putri , Nur Laila (Universitas Airlangga, 2025)
Introduction: The lack of children's behavior towards compliance with the 6-step hand washing is due to the lack of education, one of which can improve it is through the educational video “GEMITA”. This community service activity aims to optimize GEMITA education in providing health education to increase knowledge, attitudes, and compliance regarding the 6 steps of hand washing. Methods: The GEMITA video for kindergarten children by the community service team of the Faculty of Health Sciences, Universitas Gresik, at Baitussholah Kindergarten School in Surabaya in April 2024. The community service team provided health information about the 6 steps of hand washing, demonstrating, with interactive discussions in small groups. Participants consisted of 41 kindergarten children aged 4-6 years. Each group consisted of 6-7 children. The activity began with a pre-test using an observation and got education through a 10-minute GEMITA video and handwashing demonstration. After that, a post-test was conducted to evaluate the program. Results: The knowledge in the good category (65.9%) after receiving health education through the GEMITA video. There was also a change in attitude in the good category (80.5%), and 41% of kindergarten children experienced increased compliance in the compliant category. Conclusion: Health education through the GEMITA video has proven effective in increasing knowledge, attitudes, and compliance of children in following health education. Providing the GEMITA video is recommended to become a routine school program for kindergarten that maintains children's cleanliness and health behavior through health education activities and the way to wash hands.